Kajian Literatur: Berpengaruhkah Peran Kepala Sekolah Dengan Kedisiplinan Kinerja Guru? - Putri, Loly Nadila; Masbirorotni, Masbirorotni; Sutriyanti, Sutriyanti (Universitas Batanghari Jambi, 2024)
This literature review aims to explore the influence of the role of the principal on teacher performance discipline. Based on literature reviews and previous research, the role of the principal is considered an important factor in teacher performance discipline. Discipline is very important in efforts to improve teacher performance, meaning that the higher the work discipline, the higher the performance. Thus it can be said that the relationship between work discipline and teacher performance is positive. The research method used is a literature study by collecting and analyzing articles, journals and books related to the influence of the role of the principal on teacher performance discipline. The results of the literature review show that the role of the principal has a significant influence on teacher performance discipline. School principals have an important role in improving teacher discipline through coaching, motivation and example. Steps taken by school principals to improve teacher discipline include making rules, regulations, activity procedures, setting activity hours, and motivating teachers. The higher a teacher's work discipline, the better the teacher's performance will be